PROBLEMS OF SPEECH CULTURE IN MODERN SOCIETY - Khatamov Ildar Urakovich (Western European Studies, 2024)
The article examines the changes taking place in the language at the present stage; analyzes the prerequisites that led to the problems of speech culture. The author examines the main trends in the development of the language, highlighting among them the saturation of the language with borrowings, nonliterary vocabulary, violations of speech norms. The article is of interest both for linguists and for students of philological and non-philological universities, since the problems of the modern Russian literary language are relevant and affect the sphere of interests of the entire people
Keywords: speech; borrowed vocabulary; speech culture